2021
DOI: 10.1186/s13098-020-00620-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between metabolic syndrome and type of dementia: analysis based on the National Health Insurance Service database of Gangwon province in South Korea

Abstract: Background Metabolic syndrome is a cluster of conditions that occur together, increasing the risk of cardiovascular disease. However, the relationship between metabolic syndrome and dementia has remained controversial. Using nationwide population cohort data, we investigated the association between metabolic syndrome and dementia, according to the dementia type. Methods We analyzed data of 84,144 individuals, in the aged group of more than 60 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 85 publications
1
29
0
1
Order By: Relevance
“… 85 The vWAT accumulation significantly increased the long-term risk of AD in normal elderly people over 60 years of age. 86 Compared with age- and sex-matched controls, patients with mild-to-moderate AD had significantly higher vWAT mass, and the correlation was more pronounced in male AD patients. 87 A prospective study of asymptomatic middle-aged adults with risk factors for AD showed that the vWAT accumulation was significantly associated with decline of brain Aβ burden, language learning and language memory.…”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 90%
“… 85 The vWAT accumulation significantly increased the long-term risk of AD in normal elderly people over 60 years of age. 86 Compared with age- and sex-matched controls, patients with mild-to-moderate AD had significantly higher vWAT mass, and the correlation was more pronounced in male AD patients. 87 A prospective study of asymptomatic middle-aged adults with risk factors for AD showed that the vWAT accumulation was significantly associated with decline of brain Aβ burden, language learning and language memory.…”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 90%
“…All models were adjusted by cardiorespiratory fitness (CRF) and metabolic status (MS), two well-established cardiometabolic risk factors for AD ( Tari et al, 2019 ; Kim et al, 2021 ). In addition, higher CRF has been associated with better executive function through changes in functional brain connectivity ( Peven et al, 2019 ), while the metabolic syndrome has been linked to poorer executive function presumably as a result of altered intrinsic communication across core neural networks and disrupted between-network connections across the brain ( Foret et al, 2021 ; Rashid et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…T2DM results in a cluster of metabolic aberrations that are well established to independently and synergistically increase risk of cardiovascular disease. In prediabetics with metabolic syndrome, Kim et al [1] explored associations between metabolic syndrome and dementia types in a nationwide population cohort of over 84 000 South Koreans. They reported that serum triglycerides, cholesterol, blood pressure, glucose, central obesity and low-HDL cholesterol increased risk for Alzheimer's >11-fold.…”
Section: Population Studies Support An Association Of Metabolic Syndr...mentioning
confidence: 99%